High-antibacterial fabric and preparation process thereof
By adopting a combined structure of composite fabric layer, antibacterial adhesion layer, zinc coating and nanosilver antibacterial layer in antibacterial fabrics, the problems of insufficient durability and reduced antibacterial effect of existing antibacterial fabrics are solved, and high-efficiency antibacterial performance and biocompatibility are achieved.
Patent Information
- Application Number
- CN202411932432.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-03-14
AI Technical Summary
The existing antibacterial fabrics have insufficient durability, rapid antibacterial effect, and some antibacterial materials are cytotoxic, making them difficult to be widely used in long-term use and medical and health fields.
Using a combined structure of composite fabric layer, anti-bacterial adhesion layer, zinc coating, cotton fabric substrate and nano-silver antibacterial layer, high-efficiency antibacterial fabrics are prepared through electrospinning and magnetron sputtering.
It achieves the improvement of efficient antibacterial properties, while ensuring the biocompatibility and washing resistance of the material, extending the service life of the fabric, and reducing the risk of cytotoxicity.
Smart Images

Figure BDA0005210678550000131 
Figure HDA0005210678560000011
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of antibacterial fabrics, in particular to a highly antibacterial fabric and a preparation process thereof. Background Art
[0002] At present, with the continuous improvement of people's awareness of health and hygiene, the application of antibacterial fabrics is becoming more and more widespread, especially in the fields of medical care, hygiene, household textiles and outdoor sports. The demand for fabrics with excellent antibacterial properties is particularly urgent. However, existing antibacterial fabrics generally have problems such as insufficient durability and rapid decline in antibacterial effect, which cannot meet people's needs for long-term use. These problems are mainly caused by the weak combination of antibacterial agents and fibers or the insufficient stability of the antibacterial materials themselves, which leads to their gradual ineffectiveness during use or washing. In addition, some antibacterial materials have strong cytotoxicity, which inhibits bacteria while also posing certain potential risks to human health.
[0003] Current antibacterial fabrics are usually coated with chemicals or nanoparticles to impart antibacterial properties. However, due to the instability of these coating materials in physical or chemical environments, they have poor durability during use and are difficult to withstand multiple washes. At the same time, some antibacterial ingredients are biotoxic or skin irritating, and cannot be widely used in fabrics that come into direct contact with the human body. In particular, the medical and health fields place strict requirements on their safety and durability. Traditional antibacterial materials are difficult to ensure long-term antibacterial effects while also being safe and comfortable.
[0004] Therefore, there is an urgent need for an antibacterial fabric with high antibacterial ability, good biocompatibility and excellent washing resistance, while ensuring that the material is non-cytotoxic to the human body to meet people's higher requirements for antibacterial fabrics. This can not only improve the service life and safety of the fabric, but also meet the strict requirements of antibacterial, hygiene and health in specific fields. Summary of the invention
[0005] The purpose of the present invention is to provide a highly antibacterial fabric and a preparation process thereof to solve the problems raised in the prior art.
[0006] To achieve the above object, the present invention provides the following technical solutions:
[0007] A highly antibacterial fabric comprises a composite fabric layer, an antibacterial adhesion layer, a zinc coating, a cotton fabric substrate and a nano-silver antibacterial layer; the composite fabric layer is prepared by electrostatic spinning of polycaprolactone spinning solution and polylactic acid spinning solution, the polycaprolactone spinning solution is prepared by mixing a polycaprolactone solution and a composite heterojunction suspension, the composite heterojunction in the composite heterojunction suspension is prepared by a hydrothermal method from sodium molybdate dihydrate and zinc; the antibacterial adhesion layer is prepared by menthol-modified polyacrylate; the zinc coating is prepared by magnetron sputtering of a zinc target; and the nano-silver antibacterial layer is prepared by in-situ reduction of silver nitrate from hinokitiol-modified chitosan.
[0008] Furthermore, the method for preparing the composite heterojunction comprises the following steps:
[0009] Sodium molybdate dihydrate and thioacetamide are added to deionized water, stirred at a speed of 600-800 rpm for 30-35 minutes, zinc is added, stirred at a speed of 600-800 rpm for 15-20 minutes, the mixed solution is transferred to an autoclave, heated to 220-225° C. for 12 hours, cooled to room temperature, centrifuged, the centrifuged solid product is washed with deionized water and ethanol, and vacuum dried at 60-65° C. for 6-6.5 hours to obtain a composite heterojunction; in the preparation process of the composite heterojunction, the mass ratio of sodium molybdate dihydrate: thioacetamide: zinc is 1.24:2.31:1.
[0010] Furthermore, the preparation method of the menthol modified polyacrylate comprises the following steps:
[0011] Acrylic anhydride and 2 wt% 4-dimethylaminopyridine are added to tetrahydrofuran, heated to 70-72°C and stirred evenly, menthol is added, the reaction is kept warm for 5-6 hours, ammonium persulfate is added, the reaction is kept warm for 4-4.5 hours, cooled, vacuum filtered, washed with ether, and vacuum dried to obtain a menthol antibacterial adhesive; in the preparation process of the menthol antibacterial adhesive, the molar ratio of menthol: acrylic anhydride is (2-2.5):1.
[0012] Furthermore, the method for preparing the hinokitiol-modified chitosan comprises the following steps:
[0013] Chitosan is added to 2% v / v acetic acid, heated to 80-82° C. and stirred evenly, paraformaldehyde is added, stirred evenly, hinokitiol is added, the reaction is kept warm, ether is used for extraction, and rotary evaporation is performed to obtain hinokitiol-modified chitosan; in the preparation process of hinokitiol-modified chitosan, the molar ratio of hinokitiol: paraformaldehyde is 1:1; the molar ratio of hinokitiol: chitosan is 2:1.
[0014] Furthermore, in the preparation process of hinokitiol-modified chitosan, the reaction endpoint is monitored by thin layer chromatography during the heat preservation reaction process, and n-hexane and ethyl acetate with a volume ratio of 1:1 are used as developing solvents to compare the spots of the raw materials before and after the reaction. When the spots of the raw materials disappear or remain stable, it indicates that the reaction is over; the ether extraction is to use ether to extract the reaction product until there are no raw material spots monitored by thin layer chromatography.
[0015] A preparation process of a highly antibacterial fabric comprises the following steps: S1: using magnetron sputtering to deposit zinc on the surface of a cotton fabric substrate to obtain a zinc coating;
[0016] S2: adding menthol-modified polyacrylate and 4-dimethylaminopyridine into deionized water, stirring evenly, coating on the surface of the zinc coating, and drying at 80-90° C. for 3-5 min to obtain an antibacterial adhesion layer;
[0017] S3: adding polycaprolactone to the mixed solvent, heating to 30-32°C and stirring evenly to obtain a polycaprolactone solution; adding the composite heterojunction to the mixed solvent, ultrasonically dispersing, and obtaining a suspension; adding the suspension to the polycaprolactone solution, stirring evenly, and obtaining a polycaprolactone spinning solution; adding polylactic acid to the mixed solvent, stirring evenly, and obtaining a polylactic acid spinning solution; electrostatically spinning the polycaprolactone spinning solution and the polylactic acid spinning solution on the bacterial adhesion layer to obtain a composite fabric layer;
[0018] S4: adding silver nitrate solution to 40% v / v hinokitiol modified chitosan solution, heating to 80-85°C for reaction for 15-20min, adding aloe extract, keeping warm for reaction for 6-6.5h, cooling, centrifuging and separating to obtain nano silver antibacterial agent; applying citric acid solution to the side of cotton fabric substrate 4 away from zinc coating 3, drying at 80-85°C for 3min, drying at 140-142°C for 2min, applying nano silver antibacterial agent, drying at 80-85°C for 3min, drying at 140-142°C for 2min, obtaining nano silver antibacterial layer, and preparing highly antibacterial fabric.
[0019] Furthermore, in step S1, the magnetron sputtering parameters include: an operating power of 40-60 W, a flow rate of 15 sccm, a gas flow consisting of argon and oxygen in a volume ratio of 1:1, and a sputtering time of 5 min.
[0020] Furthermore, in step S2, the amount of polyol-modified polyacrylate added is 20 g per 1 L of deionized water, the amount of 4-dimethylaminopyridine added is 4 g per 1 L of deionized water, and the thickness of the antibacterial adhesion layer 2 is 10-20 μm.
[0021] Furthermore, in step S3, the mixed solvent consists of tetrahydrofuran and N,N-dimethylformamide in a volume ratio of 4:1, the amount of polycaprolactone added is 62.5 g per 1 L of mixed solvent, the amount of composite heterojunction added is 30-40 wt% of the mass of polycaprolactone, and the amount of polylactic acid added is 80 g per 1 L of mixed solvent. The electrospinning parameters include: the inner diameter of the needle is 0.4 mm, the injection rate is 0.8 mL / h, the receiving distance is 25 cm, the applied voltage is 25 kV, the collector rotation rate is 50 rpm, the operating temperature is 21-25 ° C, the relative humidity is 33-37%, and the injection ratio of polylactic acid spinning solution: polycaprolactone spinning solution is (2-3): (1-2).
[0022] Furthermore, in step S4, the concentration of the silver nitrate solution is 0.235 mol / L, the volume ratio of 40% v / v hinokitiol modified chitosan solution: silver nitrate solution: aloe extract is 10:(6-8):3, the concentration of the citric acid solution is 2.5 g / L, and the thickness of the nanosilver antibacterial layer 5 is 20-40 μm.
[0023] Furthermore, the preparation process of the aloe extract includes the following steps: crushing the aloe leaves into a thin paste, adding deionized water, heating to 100-102°C for 15-20 minutes, cooling, filtering, removing solid impurities, and storing the filtered solution at 0°C to obtain the aloe extract; in the preparation process of the aloe extract, the mass ratio of aloe leaves: deionized water is 2:1.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] 1. The present invention grafts natural hinokitiol onto chitosan through the Mannich reaction, and then loads nanosilver through in-situ reduction to prepare a nanosilver antibacterial agent; uses citric acid as a cross-linking agent to form a nanosilver antibacterial layer on the surface of a cotton fabric substrate, and combines it with a zinc coating prepared by magnetron sputtering on the other side of the cotton fabric substrate, and uses external water vapor to generate water and electricity stimulation inside the fabric, thereby greatly enhancing the antibacterial function of the fabric. With the help of water vapor, Ag x The structure of the O-Zn microbattery provides positive charge, which releases a large amount of Ag + and Zn 2+ It combines with negatively charged proteases to effectively pierce the bacterial cell walls, thereby destroying the bacteria and achieving an antibacterial effect. At the same time, the released Ag and Zn ions have no effect on the metabolism of fibroblasts, and the released metal ions are not cytotoxic. The difference from traditional double-sided magnetron sputtering of Ag and Zn is that the nano-silver antibacterial layer of the present invention retains the antibacterial properties of hydroelectric stimulation while having excellent hydrophilic and skin-friendly properties, perfectly meeting people's needs for daily wear and skin contact, and greatly expanding the scope of application.
[0026] 2. On this basis, the present invention successfully prepares a composite heterojunction by a hydrothermal method, and prepares a biodegradable composite fabric layer based on polycaprolactone and polylactic acid by electrospinning. By controlling the injection ratio of polycaprolactone spinning solution and polylactic acid spinning solution, the porosity, air permeability and fracture stress of the composite fabric layer are adjusted so that it has the best air permeability while meeting the fracture stress. At the same time, the composite heterojunction is introduced into the polycaprolactone spinning solution. The composite heterojunction inhibits the recombination of photogenerated electron-hole pairs and promotes charge transfer, while improving the hydrophobicity of polycaprolactone. The composite heterojunction gives the composite fabric layer excellent photothermal and photocatalytic properties under visible light, and effectively kills bacteria by utilizing the synergistic effect of high temperature and active oxygen, further improving the antibacterial properties of the fabric.
[0027] 3. An antibacterial adhesion layer made of menthol-modified polyacrylate is set between the composite fabric layer and the zinc coating. On the one hand, it prevents dead bacterial cells from further damaging the fabric fibers, prolongs the service life of the antibacterial fabric, and enhances the antibacterial properties; on the other hand, the bonding layer between the composite fabric layer and the zinc coating further enhances the durability of the antibacterial fabric. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is a schematic diagram of the structure of the highly antibacterial fabric of the present invention;
[0029] Among them, there are a composite fabric layer 1, an antibacterial adhesion layer 2, a zinc coating 3, a cotton fabric substrate 4, and a nano-silver antibacterial layer 5. DETAILED DESCRIPTION
[0030] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0031] In the following embodiments, the method for preparing the composite heterojunction comprises the following steps:
[0032] Sodium molybdate dihydrate and thioacetamide are added to deionized water, stirred at 600 rpm for 30 minutes, zinc is added, stirred at 600 rpm for 15 minutes, the mixed solution is transferred to an autoclave, heated to 220°C for 12 hours, cooled to room temperature, centrifuged, the centrifuged solid product is washed with deionized water and ethanol, and vacuum dried at 60°C for 6 hours to obtain a composite heterojunction; in the preparation process of the composite heterojunction, the mass ratio of sodium molybdate dihydrate: thioacetamide: zinc is 1.24:2.31:1.
[0033] In the following examples, the preparation method of menthol modified polyacrylate comprises the following steps:
[0034] Acrylic anhydride and 2 wt% 4-dimethylaminopyridine are added to tetrahydrofuran, heated to 70°C and stirred evenly, menthol is added, the reaction is kept warm for 5 hours, ammonium persulfate is added, the reaction is kept warm for 4 hours, cooled, vacuum filtered, washed with ether, and vacuum dried to obtain a menthol antibacterial adhesive; in the preparation process of the menthol antibacterial adhesive, the molar ratio of menthol: acrylic anhydride is 2:1.
[0035] In the following examples, the preparation method of hinokitiol-modified chitosan comprises the following steps:
[0036] Chitosan is added to 2% v / v acetic acid, heated to 80°C and stirred evenly, paraformaldehyde is added, stirred evenly, hinokitiol is added, the mixture is kept warm for reaction, ether is used for extraction, and rotary evaporation is performed to obtain hinokitiol-modified chitosan; in the preparation process of hinokitiol-modified chitosan, the molar ratio of hinokitiol: paraformaldehyde is 1:1; the molar ratio of hinokitiol: chitosan is 2:1.
[0037] The preparation process of aloe extract comprises the following steps: crushing aloe leaves into a thin paste, adding deionized water, heating to 100°C for 15 minutes, cooling, filtering, removing solid impurities, and storing the filtered solution at 0°C to obtain aloe extract; in the preparation process of aloe extract, the mass ratio of aloe leaves to deionized water is 2:1.
[0038] Example 1: A process for preparing a highly antibacterial fabric: comprising the following steps: S1: using magnetron sputtering to deposit zinc on the surface of a cotton fabric substrate 4 to obtain a zinc coating 3;
[0039] The magnetron sputtering parameters included: operating power of 40 W, flow rate of 15 sccm, gas flow consisting of argon and oxygen in a volume ratio of 1:1, and sputtering time of 5 min;
[0040] S2: adding menthol-modified polyacrylate and 4-dimethylaminopyridine into deionized water, stirring evenly, coating on the surface of the zinc coating 3, and drying at 80-90° C. for 3-5 min to obtain an antibacterial adhesion layer 2;
[0041] The thickness of the antibacterial adhesion layer 2 is 20 μm;
[0042] S3: adding polycaprolactone to the mixed solvent, heating to 30-32°C and stirring evenly to obtain a polycaprolactone solution; adding the composite heterojunction to the mixed solvent, ultrasonically dispersing, and obtaining a suspension; adding the suspension to the polycaprolactone solution, stirring evenly, and obtaining a polycaprolactone spinning solution; adding polylactic acid to the mixed solvent, stirring evenly, and obtaining a polylactic acid spinning solution; electrostatically spinning the polycaprolactone spinning solution and the polylactic acid spinning solution on the bacterial adhesion layer 2 to obtain a composite fabric layer 1;
[0043] The amount of polycaprolactone added is 62.5 g per 1 L of mixed solvent, the amount of composite heterojunction added is 30 wt% of the mass of polycaprolactone, and the amount of polylactic acid added is 80 g per 1 L of mixed solvent. The electrospinning parameters include: the inner diameter of the needle is 0.4 mm, the injection rate is 0.8 mL / h, the receiving distance is 25 cm, the applied voltage is 25 kV, the collector rotation rate is 50 rpm, the working temperature is 21-25 ° C, the relative humidity is 33-37%, and the injection ratio of polylactic acid spinning solution: polycaprolactone spinning solution is 2:1;
[0044] S4: adding silver nitrate solution to 40% v / v hinokitiol modified chitosan solution, heating to 80-85°C for reaction for 15-20 min, adding aloe extract, keeping warm for reaction for 6-6.5 h, cooling, centrifuging and separating to obtain nano silver antibacterial agent; applying citric acid solution to the side of cotton fabric substrate 4 away from zinc coating 3, drying at 80-85°C for 3 min, drying at 140-142°C for 2 min, applying nano silver antibacterial agent, drying at 80-85°C for 3 min, drying at 140-142°C for 2 min, obtaining nano silver antibacterial layer 5, and preparing highly antibacterial fabric.
[0045] The concentration of the silver nitrate solution is 0.235 mol / L, the volume ratio of 40% v / v hinokitiol modified chitosan solution: silver nitrate solution: aloe extract is 10:6:3, the concentration of the citric acid solution is 2.5 g / L, and the thickness of the nanosilver antibacterial layer 5 is 40 μm.
[0046] Example 2: A process for preparing a highly antibacterial fabric: comprising the following steps: S1: using magnetron sputtering to deposit zinc on the surface of a cotton fabric substrate 4 to obtain a zinc coating 3;
[0047] The magnetron sputtering parameters included: operating power of 60 W, flow rate of 15 sccm, gas flow consisting of argon and oxygen in a volume ratio of 1:1, and sputtering time of 5 min;
[0048] S2: adding menthol-modified polyacrylate and 4-dimethylaminopyridine into deionized water, stirring evenly, coating on the surface of the zinc coating 3, and drying at 80-90° C. for 3-5 min to obtain an antibacterial adhesion layer 2;
[0049] The thickness of the antibacterial adhesion layer 2 is 20 μm;
[0050] S3: adding polycaprolactone to the mixed solvent, heating to 30-32°C and stirring evenly to obtain a polycaprolactone solution; adding the composite heterojunction to the mixed solvent, ultrasonically dispersing, and obtaining a suspension; adding the suspension to the polycaprolactone solution, stirring evenly, and obtaining a polycaprolactone spinning solution; adding polylactic acid to the mixed solvent, stirring evenly, and obtaining a polylactic acid spinning solution; electrostatically spinning the polycaprolactone spinning solution and the polylactic acid spinning solution on the bacterial adhesion layer 2 to obtain a composite fabric layer 1;
[0051] The amount of polycaprolactone added is 62.5 g per 1 L of mixed solvent, the amount of composite heterojunction added is 40 wt% of the mass of polycaprolactone, and the amount of polylactic acid added is 80 g per 1 L of mixed solvent. The electrospinning parameters include: the inner diameter of the needle is 0.4 mm, the injection rate is 0.8 mL / h, the receiving distance is 25 cm, the applied voltage is 25 kV, the collector rotation rate is 50 rpm, the working temperature is 21-25 ° C, the relative humidity is 33-37%, and the injection ratio of polylactic acid spinning solution: polycaprolactone spinning solution is 2:1;
[0052] S4: adding silver nitrate solution to 40% v / v hinokitiol modified chitosan solution, heating to 80-85°C for reaction for 15-20 min, adding aloe extract, keeping warm for reaction for 6-6.5 h, cooling, centrifuging and separating to obtain nano silver antibacterial agent; applying citric acid solution to the side of cotton fabric substrate 4 away from zinc coating 3, drying at 80-85°C for 3 min, drying at 140-142°C for 2 min, applying nano silver antibacterial agent, drying at 80-85°C for 3 min, drying at 140-142°C for 2 min, obtaining nano silver antibacterial layer 5, and preparing highly antibacterial fabric.
[0053] The concentration of the silver nitrate solution is 0.235 mol / L, the volume ratio of 40% v / v hinokitiol modified chitosan solution: silver nitrate solution: aloe extract is 10:7:3, the concentration of the citric acid solution is 2.5 g / L, and the thickness of the nanosilver antibacterial layer 5 is 40 μm.
[0054] Example 3: A process for preparing a highly antibacterial fabric: comprising the following steps: S1: using magnetron sputtering to deposit zinc on the surface of a cotton fabric substrate 4 to obtain a zinc coating 3;
[0055] The magnetron sputtering parameters included: operating power of 60 W, flow rate of 15 sccm, gas flow consisting of argon and oxygen in a volume ratio of 1:1, and sputtering time of 5 min;
[0056] S2: adding menthol-modified polyacrylate and 4-dimethylaminopyridine into deionized water, stirring evenly, coating on the surface of the zinc coating 3, and drying at 80-90° C. for 3-5 min to obtain an antibacterial adhesion layer 2;
[0057] The thickness of the antibacterial adhesion layer 2 is 20 μm;
[0058] S3: adding polycaprolactone to the mixed solvent, heating to 30-32°C and stirring evenly to obtain a polycaprolactone solution; adding the composite heterojunction to the mixed solvent, ultrasonically dispersing, and obtaining a suspension; adding the suspension to the polycaprolactone solution, stirring evenly, and obtaining a polycaprolactone spinning solution; adding polylactic acid to the mixed solvent, stirring evenly, and obtaining a polylactic acid spinning solution; electrostatically spinning the polycaprolactone spinning solution and the polylactic acid spinning solution on the bacterial adhesion layer 2 to obtain a composite fabric layer 1;
[0059] The amount of polycaprolactone added is 62.5 g per 1 L of mixed solvent, the amount of composite heterojunction added is 40 wt% of the mass of polycaprolactone, and the amount of polylactic acid added is 80 g per 1 L of mixed solvent. The electrospinning parameters include: the inner diameter of the needle is 0.4 mm, the injection rate is 0.8 mL / h, the receiving distance is 25 cm, the applied voltage is 25 kV, the collector rotation rate is 50 rpm, the working temperature is 21-25 ° C, the relative humidity is 33-37%, and the injection ratio of polylactic acid spinning solution: polycaprolactone spinning solution is 3:2;
[0060] S4: adding silver nitrate solution to 40% v / v hinokitiol modified chitosan solution, heating to 80-85°C for reaction for 15-20 min, adding aloe extract, keeping warm for reaction for 6-6.5 h, cooling, centrifuging and separating to obtain nano silver antibacterial agent; applying citric acid solution to the side of cotton fabric substrate 4 away from zinc coating 3, drying at 80-85°C for 3 min, drying at 140-142°C for 2 min, applying nano silver antibacterial agent, drying at 80-85°C for 3 min, drying at 140-142°C for 2 min, obtaining nano silver antibacterial layer 5, and preparing highly antibacterial fabric.
[0061] The concentration of the silver nitrate solution is 0.235 mol / L, the volume ratio of 40% v / v hinokitiol modified chitosan solution: silver nitrate solution: aloe extract is 10:8:3, the concentration of the citric acid solution is 2.5 g / L, and the thickness of the nanosilver antibacterial layer 5 is 40 μm.
[0062] Comparative Example 1: A process for preparing a highly antibacterial fabric: comprising the following steps: S1: using magnetron sputtering to deposit zinc on the surface of a cotton fabric substrate 4 to obtain a zinc coating 3;
[0063] The magnetron sputtering parameters included: operating power of 20 W, flow rate of 15 sccm, gas flow consisting of argon and oxygen in a volume ratio of 1:1, and sputtering time of 5 min;
[0064] The remaining steps are the same as those in Example 1.
[0065] Comparative Example 2: A preparation process of a highly antibacterial fabric: S3: Add polycaprolactone to a mixed solvent, heat to 30-32°C and stir evenly to obtain a polycaprolactone solution; add the composite heterojunction to the mixed solvent, ultrasonically disperse, and obtain a suspension; add the suspension to the polycaprolactone solution, stir evenly, and obtain a polycaprolactone spinning solution; add polylactic acid to the mixed solvent, stir evenly, and obtain a polylactic acid spinning solution; electrostatically spin the polycaprolactone spinning solution and the polylactic acid spinning solution on the bacterial adhesion layer 2 to obtain a composite fabric layer 1;
[0066] The amount of polycaprolactone added is 62.5 g per 1 L of mixed solvent, the amount of composite heterojunction added is 20 wt% of the mass of polycaprolactone, and the amount of polylactic acid added is 80 g per 1 L of mixed solvent. The electrospinning parameters include: the inner diameter of the needle is 0.4 mm, the injection rate is 0.8 mL / h, the receiving distance is 25 cm, the applied voltage is 25 kV, the collector rotation rate is 50 rpm, the working temperature is 21-25 ° C, the relative humidity is 33-37%, and the injection ratio of polylactic acid spinning solution: polycaprolactone spinning solution is 2:1;
[0067] The remaining steps are the same as those in Example 1.
[0068] Comparative Example 3: A preparation process of a highly antibacterial fabric: S3: Add polycaprolactone to a mixed solvent, heat to 30-32°C and stir evenly to obtain a polycaprolactone solution; add the composite heterojunction to the mixed solvent, ultrasonically disperse, and obtain a suspension; add the suspension to the polycaprolactone solution, stir evenly, and obtain a polycaprolactone spinning solution; add polylactic acid to the mixed solvent, stir evenly, and obtain a polylactic acid spinning solution; electrostatically spin the polycaprolactone spinning solution and the polylactic acid spinning solution on the bacterial adhesion layer 2 to obtain a composite fabric layer 1;
[0069] The amount of polycaprolactone added is 62.5 g per 1 L of mixed solvent, the amount of composite heterojunction added is 30 wt% of the mass of polycaprolactone, and the amount of polylactic acid added is 80 g per 1 L of mixed solvent. The electrospinning parameters include: the inner diameter of the needle is 0.4 mm, the injection rate is 0.8 mL / h, the receiving distance is 25 cm, the applied voltage is 25 kV, the collector rotation rate is 50 rpm, the working temperature is 21-25 ° C, the relative humidity is 33-37%, and the injection ratio of polylactic acid spinning solution: polycaprolactone spinning solution is 2:2;
[0070] The remaining steps are the same as those in Example 1.
[0071] Comparative Example 4: A preparation process for a highly antibacterial fabric: S4: Add a silver nitrate solution to a 40% v / v hinokitiol-modified chitosan solution, heat to 80-85°C for reaction for 15-20 min, add an aloe extract, keep warm for reaction for 6-6.5 h, cool, and centrifuge to obtain a nano-silver antibacterial agent; apply a citric acid solution to a side of a cotton fabric substrate 4 away from a zinc coating 3, dry at 80-85°C for 3 min, dry at 140-142°C for 2 min, apply a nano-silver antibacterial agent, dry at 80-85°C for 3 min, and dry at 140-142°C for 2 min to obtain a nano-silver antibacterial layer 5, and prepare a highly antibacterial fabric.
[0072] The concentration of the silver nitrate solution is 0.235 mol / L, the volume ratio of 40% v / v hinokitiol modified chitosan solution: silver nitrate solution: aloe extract is 10:4:3, the concentration of the citric acid solution is 2.5 g / L, and the thickness of the nanosilver antibacterial layer 5 is 40 μm;
[0073] The remaining steps are the same as those in Example 1.
[0074] Experiment: Antibacterial performance: (1) Light antibacterial performance: Staphylococcus aureus and Escherichia coli were used as experimental strains, representing typical Gram-positive bacteria and Gram-negative bacteria, respectively. The highly antibacterial fabric samples were cut into 48-well plates, 80 μL of diluted bacterial solution was added to the 48-well plates of the samples, and light was applied (xenon lamp, 0.2 W cm -2 ) and dark treatment for 10 minutes, 20 μL of the mixture in the well plate was evenly spread on the agar plate and placed in an incubator at 37°C. The antibacterial efficiency was calculated by counting the number of colonies according to the following formula;
[0075] Antibacterial rate (%) = (total number of bacterial colonies in the blank group - total number of bacterial colonies in the experimental group) / (total number of bacterial colonies in the blank group) × 100%;
[0076] (2) Wet antibacterial performance: The antibacterial activity of the samples against Escherichia coli and Staphylococcus aureus was tested using an agar diffusion test to measure the antibacterial diameter;
[0077] Air permeability: The air permeability of the high antibacterial fabric samples was tested using an air permeability tester with a pressure of 200Pa and a test area of 20cm 2 ;
[0078] Mechanical properties: An electronic universal testing system was used to test the mechanical properties of the composite fabric layer of the high antibacterial fabric samples.
[0079] Table 1 High antibacterial fabric performance test data table
[0080]
[0081] Conclusion: The highly antibacterial fabric prepared by the present invention has excellent antibacterial performance and breathability.
[0082] In comparative example 1, the magnetron sputtering operating power is low, the zinc coating content is reduced, and the antibacterial diameter is reduced; in comparative example 2, the amount of composite heterojunction added is low, and the light antibacterial rate is reduced; in comparative example 3, the injection ratio of polycaprolactone spinning solution is increased, resulting in reduced air permeability and fracture stress; in comparative example 4, the volume ratio of silver nitrate solution is reduced, resulting in a reduction in antibacterial diameter.
[0083] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered exemplary and non-limiting in all respects, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations falling within the meaning and scope of the equivalent elements of the claims be included in the invention. Any reference numeral in a claim should not be considered as limiting the claim to which it relates.
Claims
1. A highly antibacterial fabric, characterized in that: The highly antibacterial fabric comprises a composite fabric layer (1), an antibacterial adhesion layer (2), a zinc coating (3), a cotton fabric substrate (4), and a nano-silver antibacterial layer (5); the composite fabric layer (1) is prepared by electrostatic spinning of a polycaprolactone spinning solution and a polylactic acid spinning solution, the polycaprolactone spinning solution is prepared by mixing a polycaprolactone solution and a composite heterojunction suspension, and the composite heterojunction in the composite heterojunction suspension is prepared by a hydrothermal method from sodium molybdate dihydrate and zinc; the antibacterial adhesion layer (2) is prepared by menthol-modified polyacrylate; the zinc coating (3) is prepared by magnetron sputtering of a zinc target; and the nano-silver antibacterial layer (5) is prepared by in-situ reduction of silver nitrate from hinokitiol-modified chitosan.
2. The highly antibacterial fabric according to claim 1, characterized in that: The method for preparing the composite heterojunction comprises the following steps: Sodium molybdate dihydrate and thioacetamide are added to deionized water, stirred for 30-35 minutes, zinc is added, stirred for 15-20 minutes, the mixed solution is transferred to an autoclave, heated to 220-225° C. for 12 hours, cooled to room temperature, centrifuged, the centrifuged solid product is washed with deionized water and ethanol, and vacuum dried at 60-65° C. for 6-6.5 hours to obtain a composite heterojunction; in the preparation process of the composite heterojunction, the mass ratio of sodium molybdate dihydrate: thioacetamide: zinc is 1.24:2.31:
1.
3. The highly antibacterial fabric according to claim 1, characterized in that: The preparation method of the menthol modified polyacrylate comprises the following steps: Acrylic anhydride and 2 wt% 4-dimethylaminopyridine are added to tetrahydrofuran, heated to 70-72°C and stirred evenly, menthol is added, the reaction is kept warm for 5-6 hours, ammonium persulfate is added, the reaction is kept warm for 4-4.5 hours, cooled, vacuum filtered, washed with ether, and vacuum dried to obtain a menthol antibacterial adhesive; in the preparation process of the menthol antibacterial adhesive, the molar ratio of menthol: acrylic anhydride is (2-2.5):
1.
4. The highly antibacterial fabric according to claim 1, characterized in that: The method for preparing hinokitiol-modified chitosan comprises the following steps: Chitosan is added to 2% v / v acetic acid, heated to 80-82° C. and stirred evenly, paraformaldehyde is added, stirred evenly, hinokitiol is added, the reaction is kept warm, ether is used for extraction, and rotary evaporation is performed to obtain hinokitiol-modified chitosan; in the preparation process of hinokitiol-modified chitosan, the molar ratio of hinokitiol: paraformaldehyde is 1:1; the molar ratio of hinokitiol: chitosan is 2:
1.
5. The preparation process of a highly antibacterial fabric according to claim 1, characterized in that: The following steps are involved: S1: using magnetron sputtering to deposit zinc on the surface of a cotton fabric substrate (4) to obtain a zinc coating (3); S2: adding menthol-modified polyacrylate and 4-dimethylaminopyridine into deionized water, stirring evenly, coating on the surface of the zinc coating (3), and drying at 80-90° C. for 3-5 minutes to obtain an antibacterial adhesion layer (2); S3: adding polycaprolactone to a mixed solvent, heating to 30-32°C and stirring evenly to obtain a polycaprolactone solution; adding the composite heterojunction to the mixed solvent, ultrasonically dispersing, and obtaining a suspension; adding the suspension to the polycaprolactone solution and stirring evenly to obtain a polycaprolactone spinning solution; adding polylactic acid to the mixed solvent and stirring evenly to obtain a polylactic acid spinning solution; electrostatically spinning the polycaprolactone spinning solution and the polylactic acid spinning solution on the bacterial adhesion layer (2) to obtain a composite fabric layer (1); S4: adding silver nitrate solution to 40% v / v hinokitiol modified chitosan solution, heating to 80-85°C for reaction for 15-20 minutes, adding aloe extract, keeping the temperature for reaction for 6-6.5 hours, cooling, centrifuging and separating to obtain nano silver antibacterial agent; applying citric acid solution to the side of cotton fabric substrate (4) away from zinc coating (3), drying at 80-85°C for 3 minutes, drying at 140-142°C for 2 minutes, applying nano silver antibacterial agent, drying at 80-85°C for 3 minutes, and drying at 140-142°C for 2 minutes, obtaining nano silver antibacterial layer (5), and preparing highly antibacterial fabric.
6. The process for preparing a highly antibacterial fabric according to claim 5, characterized in that: In step S1, the magnetron sputtering parameters include: working power of 40-60 W, flow rate of 15 sccm, gas flow consisting of argon and oxygen in a volume ratio of 1:1, and sputtering time of 5 min.
7. The process for preparing a highly antibacterial fabric according to claim 5, characterized in that: In step S2, the amount of polyol-modified polyacrylate added is 20 g per 1 L of deionized water, the amount of 4-dimethylaminopyridine added is 4 g per 1 L of deionized water, and the thickness of the antibacterial adhesion layer (2) is 10-20 μm.
8. The process for preparing a highly antibacterial fabric according to claim 5, characterized in that: In step S3, the mixed solvent consists of tetrahydrofuran and N,N-dimethylformamide in a volume ratio of 4:1, the amount of polycaprolactone added is 62.5g per 1L of mixed solvent, the amount of composite heterojunction added is 30-40wt% of the mass of polycaprolactone, and the amount of polylactic acid added is 80g per 1L of mixed solvent. The electrospinning parameters include: the inner diameter of the needle is 0.4mm, the injection rate is 0.8mL / h, the receiving distance is 25cm, the applied voltage is 25kV, the collector rotation rate is 50rpm, the operating temperature is 21-25°C, the relative humidity is 33-37%, and the injection ratio of polylactic acid spinning solution: polycaprolactone spinning solution is (2-3):(1-2).
9. The process for preparing a highly antibacterial fabric according to claim 5, characterized in that: In step S4, the concentration of the silver nitrate solution is 0.235 mol / L, the volume ratio of 40% v / v hinokitiol modified chitosan solution:silver nitrate solution:aloe extract is 10:(6-8):3, the concentration of the citric acid solution is 2.5 g / L, and the thickness of the nanosilver antibacterial layer (5) is 20-40 μm.
10. A highly antibacterial fabric prepared according to the preparation process of a highly antibacterial fabric according to any one of claims 5 to 9.
Citation Information
Patent Citations
Preparation method of zinc oxide / silver compound and preparation method of antibacterial cotton fabric
CN107691473A
Chitosan nano-silver composite antibacterial fabric and preparation method thereof
CN112123885A
Antibacterial functional fabric and preparation method thereof
CN113584884A
Preparation method and application of CdS / Znln2S4 heterojunction photocatalyst
CN115739123A
Ecological durable antibacterial and bacterial adhesion prevention dual-function fabric and preparation method thereof
CN116377717A
Cited By
Special-shaped medical adhesive tape and preparation method thereof
CN120924177A